A Case-control Study Examining the Characteristics of Patients who Fall in an Inpatient Traumatic Brain Injury Rehabilitation Setting. Issue 2 (March 2016) - McKechnie, Duncan; Fisher, Murray J.; Pryor, Julie
Abstract : Objective: The purpose of the study was to describe the characteristics of patients who fall in the inpatient traumatic brain injury (TBI) rehabilitation setting. Setting: Specialized inpatient TBI rehabilitation unit. Participants: Fifty-four patients with history of falls and 55 nonequivalent patients without history of falls. Design: Retrospective nonequivalent case-control study. Main Measures: The Functional Independence Measure, Glasgow Coma Scale, Westmead Post-traumatic Amnesia Scale, demographic and functional characteristics, and behavior and medication variables. Results: No significant difference between patients with and without history of falls for age, sex, medication class or total number of medications administered on admission, and median admission Westmead Post-traumatic Amnesia Scale score was observed. Patients with history of falls had a significantly longer duration of post-traumatic amnesia, rehabilitation length of stay, and lower mean total admission Functional Independence Measure score and median Glasgow Coma Scale score at the time of injury. Patients with history of falls were more than 10 times more likely than patients without history of falls to require assistance on admission for activities of daily living, transfers, and continence/toileting. Neurobehaviors including noncompliance and anosognosia were significantly associated with patients with history of falls. Conclusions: A patient in the rehabilitation setting with a more severe TBI characterized by multisystem impairments is at an increased risk of falling, whereas some traditional fall risk factors were not associated with patients who fall. Rehabilitation settings should consider cohort-specific fall risk profiling. The Ontario STRATIFY Falls Risk Screening Tool is perhaps not the best tool to screen for falls in this inpatient population.